Pelaksanaan Liturgi, Puasa, dan Doa Terhadap Pertumbuhan Kerohanian Jemaat Berdasarkan Daniel 9:3-5 - Tampubolon, Amrin; Hendriks, Alvyn C. (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study explores the impact of the implementation of liturgy, fasting, and prayer on the spiritual growth of the congregation in the Seventh-day Adventist Church (SDA) in the South Simalungun One District. The primary objective is to understand, analyze, and examine how the practices of liturgy, fasting, and prayer influence spiritual development. The research employs descriptive analysis and causal relationship testing, with data collected from the actual conditions of the studied population. It examines the relationship between independent variables (liturgy, fasting, and prayer) and the dependent variable (spiritual growth). Findings reveal that the practice of liturgy has a strong correlation with spiritual growth—greater participation in liturgical practices contributes significantly to the development of the congregation’s spirituality. Similarly, the practices of fasting and prayer are shown to have a substantial impact on spiritual development. The study indicates that engaging in fasting and prayer can lead believers to grow significantly in their faith and spirituality.In conclusion, liturgy, fasting, and prayer all positively contribute to the spiritual growth of the congregation. Faithfulness in service (liturgy), practicing fasting, and engaging in prayer encourage the congregation to grow spiritually, strengthen their faith, and live in love toward God and others, rooted in the love of Christ.